2019
DOI: 10.1002/cssc.201901052
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Solvent Fractionation of Lignin Enhances Carbon Fiber Performance

Abstract: Lignin is an abundantn atural polymer in plants next to cellulose, yet also am ajor industrial waste produced from both lignocellulosic biorefinery and the paper-making industry. [1] Annually,a pproximately 50 million tons of lignin waste are generated from pulping mills. [2] This lignin waste stream could be furthera dded up to 300 million tons if the billion-ton initiative for lignocellulosic biofuels is implemented. [3] Even though upgradingl ignin into value-added products has been extensively soughta ft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Likewise, the chemical features of polymer precursors in biomass feedstocks are likely to define the properties of resultant materials. This fundamental structure-property relationship between lignin chemical characteristics and carbon fiber properties was also evidenced by previous studies of manufacturing processes, where molecular weight, uniformity, linkage profile, and functional group all can potentially impact on carbon fiber properties ( Beaucamp et al., 2019 ; Culebras et al., 2018b ; Li et al., 2017a , 2017b , 2018a , 2019b ; Zhang et al., 2019 ). Despite the manufacturing process studies, it is still not clear if these chemical features can be achieved through feedstock improvement and how these chemical features are different in different feedstock cultivars, engineered lines, and growth conditions.…”
Section: Introductionsupporting
confidence: 68%
“…Likewise, the chemical features of polymer precursors in biomass feedstocks are likely to define the properties of resultant materials. This fundamental structure-property relationship between lignin chemical characteristics and carbon fiber properties was also evidenced by previous studies of manufacturing processes, where molecular weight, uniformity, linkage profile, and functional group all can potentially impact on carbon fiber properties ( Beaucamp et al., 2019 ; Culebras et al., 2018b ; Li et al., 2017a , 2017b , 2018a , 2019b ; Zhang et al., 2019 ). Despite the manufacturing process studies, it is still not clear if these chemical features can be achieved through feedstock improvement and how these chemical features are different in different feedstock cultivars, engineered lines, and growth conditions.…”
Section: Introductionsupporting
confidence: 68%
“…The acidified medium was centrifuged at 8000 rpm for 20 min, which was followed by lyophilization for lignin powders. Lignin samples (30−50 mg) and the polymers extracted from the pellets were subjected to 2D HSQC NMR analysis as described by Mansfield et al 55 The frequencies of lignin linkages and lignin units were quantified as we reported previously, 56,57 and lignin linkages were expressed as per 100 aromatic rings. Analytical Methods and Statistical Analysis.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…30–50 mg of lignin was dissolved in 0.6 mL of DMSO- d 6 and placed in the NMR tube. Adiabatic 2D 1 H– 13 C HSQC spectra were acquired on a Varian 500 MHz NMR spectrometer in the “gradient HSQCAD” mode, as reported before. , The parameters of HSQC were set at 1.0-s pulse delay, 64 scans, 1024 data points for 1 H, and 256 increments for 13 C. The central solvent peak at δC/δH = 39.5/2.49 ppm was used as the reference. For quantification of lignin linkages, the well-resolved contours of the linkages were integrated using the software MestReNova.…”
Section: Experimental Sectionmentioning
confidence: 99%